Who Wants to Grant Robots Rights? - De Graaf, Maartje M. A.; Hindriks, Frank A.; Hindriks, Koen V. (Frontiers in Robotics and AI, 2022)
The robot rights debate has thus far proceeded without any reliable data concerning the public opinion about robots and the rights they should have. We have administered an online survey (n = 200) that investigates layman’s attitudes towards granting particular rights to robots. Furthermore, we have asked them for what reasons they are willing to grant them those rights. Finally, we have administered general perceptions of robots regarding appearance, capacities, and traits. Results show that rights can be divided in sociopolitical and robot dimensions, and reasons into cognition and compassion dimensions. People generally have a positive view on robot interaction capacities. Attitudes towards robot rights depend on age and experience as well as on the cognitive and affective capacities people believe robots will ever possess. Our results suggest that the robot rights debate stands to benefit greatly from a common understanding of the capacity potentials of future robots.